Back to summation

Algebra Level 4

n = 1 1 n ( n + 1 ) ( n + 2 ) ( n + 3 ) \large \sum_{n=1}^\infty \frac1{n(n+1)(n+2)(n+3)}

If the series above equals to A B \dfrac AB where A , B A,B are coprime positive integers, then what is the value of A + B A +B ?


The answer is 19.

This section requires Javascript.
You are seeing this because something didn't load right. We suggest you, (a) try refreshing the page, (b) enabling javascript if it is disabled on your browser and, finally, (c) loading the non-javascript version of this page . We're sorry about the hassle.

3 solutions

Satvik Pandey
Aug 6, 2015

1 3 n = 1 1 n ( n + 1 ) ( n + 2 ) ( n + 3 ) × { ( n + 3 ) n } \frac { 1 }{ 3 } \sum _{ n=1 }^{ \infty }{ \frac { 1 }{ n(n+1)(n+2)(n+3) } } \times \left\{ (n+3)-n \right\}

= 1 3 [ n = 1 { 1 n ( n + 1 ) ( n + 2 ) 1 ( n + 1 ) ( n + 2 ) ( n + 3 ) } ] =\frac { 1 }{ 3 } \left[ \sum _{ n=1 }^{ \infty }{ \left\{ \frac { 1 }{ n(n+1)(n+2) } -\frac { 1 }{ (n+1)(n+2)(n+3) } \right\} } \right]

All the intermediate terms gets cancelled

= 1 3 [ 1 1.2.3 ] = 1 18 =\frac { 1 }{ 3 } \left[ \frac { 1 }{ 1.2.3 } \right] =\frac { 1 }{ 18 } .

Did the same

Aditya Kumar - 5 years ago

S = n = 1 1 n ( n + 1 ) ( n + 2 ) ( n + 3 ) Using partial fractions = n = 1 ( 1 6 n 1 2 ( n + 1 ) + 1 2 ( n + 2 ) 1 6 ( n + 3 ) ) = 1 6 n = 1 ( 1 n 3 n + 1 + 3 n + 2 1 n + 3 ) = 1 6 ( 1 1 + 1 2 + 1 3 3 2 ) = 1 18 \begin{aligned} S & = \sum_{n=1}^\infty \frac 1{n(n+1)(n+2)(n+3)} & \small \color{#3D99F6} \text{Using partial fractions} \\ & = \sum_{n=1}^\infty \left(\frac 1{6n} - \frac 1{2(n+1)} + \frac 1{2(n+2)} - \frac 1{6(n+3)} \right) \\ & = \frac 16 \sum_{n=1}^\infty \left(\frac 1{n} - \frac 3{n+1} + \frac 3{n+2} - \frac 1{n+3} \right) \\ & = \frac 16 \left(\frac 11 + \frac 12 + \frac 13 - \frac 32 \right) \\ & = \frac 1{18} \end{aligned}

A + B = 1 + 18 = 19 \implies A+B = 1+18 = \boxed{19}

Did the same way, sir!

Fidel Simanjuntak - 4 years, 2 months ago

n = 1 1 n ( n + 1 ) ( n + 2 ) ( n + 3 ) = n = 1 ( n + 3 ) n n ( n + 1 ) ( n + 2 ) ( n + 3 ) n = 1 1 3 n ( n + 1 ) ( n + 2 ) n = 1 1 3 ( n + 1 ) ( n + 2 ) ( n + 3 ) Only term with n=1 in the red series remain. All other terms cancels out. 1 3 n = 1 1 1 n ( n + 1 ) ( n + 2 ) = 1 3 ( 1 2 3 ) = A B . S o A + B = 1 + 18 = 19. \displaystyle \sum_{n=1}^{\infty} \dfrac 1 {n(n+1)(n+2)(n+3)}=\sum_{n=1}^{\infty} \dfrac {(n+3)-n}{n(n+1)(n+2)(n+3)}\\ \displaystyle {\color{#D61F06}{ \sum_{n=1}^{\infty} \dfrac 1 {3*n(n+1)(n+2)} } }-\sum_{n=1}^{\infty} \dfrac 1 {3*(n+1)(n+2)(n+3)}\\ \text{Only term with n=1 in the red series remain. All other terms cancels out.}\\ \therefore~\displaystyle \frac 1 3* \sum_{n=1}^1 \dfrac 1 {n(n+1)(n+2)} = \dfrac 1 {3*(1*2*3)}=\frac A B.~~~~~~So~~A+B=1+18=19.

0 pending reports

×

Problem Loading...

Note Loading...

Set Loading...